APPLICATION OF PHYTOREMEDIATION FOR HERBAL MEDICINE WASTE AND ITS UTILIZATION FOR PROTEIN PRODUCTION - Danny Soetrisnanto; Marcelinus Christwardana; Hadiyanto Hadiyanto (Reaktor, 2012)
Herbal industry in Indonesia is progressing very rapidly. Increasing number of herbal medicineindustries lead to an increase of the waste which are normally processed in anaerobic ponds by usingchemical and biological process. However this process are not economical feasible and therefore analternative method by using natural resource is required. Phytoremediation is an environmentalfriendly method to reduce contaminant using aquatic plant. This method uses water plant to reduceCOD and nutrients content in the waste. Since the waste still high content of nutrient, therefore it ispotential for medium growth of algae Spirulina. This study was aimed to evaluate the use of variousplant species (water hyacinth and lotus) in decreasing contaminant and to determine optimal nutrientcomposition of the growth media. The phytoremediation was performed in 3-8 days and height ofliquid in the tank was maintained constant at 5 cm. The effluent of first phytoremediation wastransferred to second stage for cultivation of Spirulina with 15 days of cultivation time. The externalnutrients were added each 2 days and the concentration of biomass was measured for its opticaldensity. Spirulina grow well in herbal medicine waste that has been phytoremediation with lotus for 3days and had a CNP ratio amounted to 57.790 : 9.281 : 1 with a growth rate of 0.271/day. Industri obat di Indonesia tumbuh sangat cepat. Pertumbuhan inimengakibatkan meningkatnya limbah yang umumnya dilakukan dalam kolam anaerobik denganmenggunakan proses kimia dan biologi. Namun demikian, proses tersebut belum menunjukkan hasilekonomis sehingga diperlukan metode lain yang relatif aman dan ekonomis. Salah satu cara yangdapat digunakan adalah phytoremediasi mengguanakn tanaman air untuk mengurangi kandunganCOD dalam limbah dan nutrient. Dikarenakan limbah masih mengandung nutrient yang cukup banyak,maka limbah tersebut juga sangat potensial untuk digunakan sebagai medium mikroalga. Penelitianini bertujuan untuk mengevaluasi penggunaan tanaman air (enceng gondok dan teratai) untukmereduksi kontaminan dalam limbah obat jamu. Phytoremediasi dilakukan selama 4-8 hari dan tinggicairan dalam reaktor dijaga pada 5 cm. Keluaran dari phytoremediasi pertama menggunakantanaman air digunakan sebagai medium di phytoremediasi menggunakan mikroalga Spirulina. Untukmendapakan pertumbuhan yang optimum, maka ditambahakan juga nutrient dan menunjukkan bahwaSpirulina tumbuh dengan sangat baik dalam medium ini. Pertumbuhan terbaik diperoleh dariphytoremediasi menggunakan teratai selama 3 hari dan kecepatan pertumbuhan 0,271/hari denganperbandingan C:N:P = 57,790:9,28:1.